Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/eco.2151
|View full text |Cite
|
Sign up to set email alerts
|

Fuels treatment and wildfire effects on runoff from Sierra Nevada mixed‐conifer forests

Abstract: We applied an eco‐hydrologic model (Regional Hydro‐Ecologic Simulation System [RHESSys]), constrained with spatially distributed field measurements, to assess the impacts of forest‐fuel treatments and wildfire on hydrologic fluxes in two Sierra Nevada firesheds. Strategically placed fuels treatments were implemented during 2011–2012 in the upper American River in the central Sierra Nevada (43 km2) and in the upper Fresno River in the southern Sierra Nevada (24 km2). This study used the measured vegetation chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…Practically, forest restoration can be limited by cost, accessibility, and ownership, which may limit the area and pace of restoration (Lydersen et al 2019;North et al 2015). We found that much of the evapotranspiration reduction (equivalent to 8±1% of the current annual evapotranspiration) occurs even in low-severity fires, implying that less-severe treatments may provide a meaningful increase in water yields (Saksa et al 2020;Saksa et al 2017).…”
Section: Sensitivity Of Evapotranspiration To Possible Increases In Fmentioning
confidence: 78%
See 2 more Smart Citations
“…Practically, forest restoration can be limited by cost, accessibility, and ownership, which may limit the area and pace of restoration (Lydersen et al 2019;North et al 2015). We found that much of the evapotranspiration reduction (equivalent to 8±1% of the current annual evapotranspiration) occurs even in low-severity fires, implying that less-severe treatments may provide a meaningful increase in water yields (Saksa et al 2020;Saksa et al 2017).…”
Section: Sensitivity Of Evapotranspiration To Possible Increases In Fmentioning
confidence: 78%
“…Likewise, analyses of actual management projects are needed. Additional factors may impact the ET after forest treatments, including changes in biomass, density, tree size and species composition can influence the post-treatment transpiration (Bart et al 2016;Roche et al 2018;Saksa et al 2020;Saksa et al 2017); treatment methods (mechanical thinning, clear cutting, with/without prescribed fires) and removing versus leaving woody debris on the ground can change evaporation demand by altering the land surface albedo and wetness (Knapp et al 2017;Stephens and Moghaddas 2005;Walker et al 2006).…”
Section: Limitations and Future Research Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…As forests are dynamic systems, water use by forests can respond in multiple ways to reductions in biomass (Tague et al, 2018). For example, Saksa et al (2019) reported a significant reduction in evapotranspiration following fuel treatment in a densely forested central Sierra Nevada area but no significant reduction in a comparable but more water-limited southern Sierra area. In the southern site, reductions in forest biomass apparently stimulated growth of remaining vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…The low level of forest thinning and contributing area treated might explain the lack of response in meadow groundwater levels. A recent modelling study of fuels treatment in the Sierra Nevada found a 3% increase in water yield in the mid-regions of the Sierra Nevada associated with an 8% reduction in vegetation [27]. However, modelling studies do not encounter the variability of field measurements.…”
Section: Annual Water Budgetmentioning
confidence: 99%